A new species of Sycorax (Diptera, Psychodidae, Sycoracinae) from the Pacific coast of Colombia (2008)
ABSTRACT: Sycorax utriensis n. sp. is described and illustrated from a male specimen collected with a CDC light trap in the Parque Nacional Natural Ensenada de Utría, on the Pacific Coast of Colombia. Five species of Sycorax are now known from Colombia, S. andicola Young, 1979, S. colombiensis Young, 1979, S. fairchildi Young, 1979, S. trispinosa Young, 1979 and S. utriensis n. sp.